Sociodemographic factors and pregnancy outcomes associated with prepregnancy obesity: effect modification of parity in the nationwide Epifane birth-cohort - Julie Boudet-Berquier; Benoit Salanave; Jean-Claude Desenclos; Katia Castetbon (BMC, 2017)
Abstract Background In light of the adverse outcomes for mothers and offspring related to maternal obesity, identification of subgroups of women at risk of prepregnancy obesity and its related-adverse issues is crucial for optimizing antenatal care. We aimed to identify sociodemographic factors and maternal and neonatal outcomes associated with prepregnancy obesity, and we tested the effect modification of parity on these associations. Methods In 2012, 3368 mothers who had delivered in 136 randomly selected maternity wards were included just after birth in the French birth cohort, Epifane. Maternal height and weight before and at the last month of pregnancy were self-reported. Maternal and neonatal outcomes were collected in medical records. Prepregnancy Body Mass Index (pBMI) was classified into underweight (<18.5), normal (18.5-24.9), overweight (25.0-29.9) and obesity (≥30.0). Since we found statistically significant interactions with parity, the multinomial logistic regression model estimating associations of pBMI class with sociodemographic characteristics and pregnancy outcomes was stratified on parity (1335 primiparous and 1814 multiparous). Results Before pregnancy, 7.6% of women were underweight, 64.2% were of normal weight, 18.0% were overweight and 10.2% were obese. Among the primiparous, maternal age of 25-29 years (OR = 2.09 [1.13-3.87]; vs. 30-34 years), high school level (OR = 2.22 [1.33-3.73]; vs. university level), gestational diabetes (OR = 2.80 [1.56-5.01]) and hypertensive complications (OR = 3.80 [1.83-7.89]) were independently associated with prepregnancy obesity. Among the multiparous, primary (OR = 6.30 [2.40-16.57]), junior high (OR = 2.89 [1.81-4.64]) and high school (OR = 1.86 [1.18-2.93]) education levels (vs. university level), no attendance at antenatal classes (OR = 1.77 [1.16-2.72]), excess gestational weight gain (OR = 1.82 [1.20-2.76]), gestational diabetes (OR =5.16 [3.15-8.46]), hypertensive complications (OR = 8.13 [3.97-16.64]), caesarean delivery (OR = 1.80 [1.18-2.77]) and infant birth weight ≥ 4 kg (OR = 1.70 [1.03-2.80]; vs. birth weight between 2.5 kg and 4 kg) were independently associated with prepregnancy obesity. Conclusion Obesity before pregnancy is associated with a set of sociodemographic characteristics and adverse pregnancy outcomes that differ across parity groups. Such findings are useful for targeted health policies aimed at attaining healthy prepregnancy weight and organizing perinatal care.